Non-noble metal catalyst Cu / TiO2-P25, preparation method thereof and application of non-noble metal catalyst Cu / TiO2-P25 in synthesis of N, N-dimethyl-p-toluidine in heterogeneous system

By loading Cu on P25 type TiO2, Cu/TiO2-P25 catalyst was prepared, which solved the problems of high raw material costs and complex processes in the prior art, and achieved low-cost and high-efficiency N,N-dimethyl-p-Art Aniline synthesis has industrial potential.

CN119386864AActive Publication Date: 2025-02-07ANHUI UNIV

Patent Information

Application Number
CN202411241762.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-02-07
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

Among the existing methods for catalytic synthesis of N,N-dimethyl p-toluidine, the raw material cost is relatively high, and the catalyst preparation process is complex, making it difficult to achieve industrialization.

Method used

The non-precious metal catalyst Cu/TiO2-P25 was used to support Cu on P25 type TiO2 by deposition-precipitation method, and a highly active catalyst was prepared, and N,N-dimethyl p-toluidine was synthesized in a heterogeneous system.

Benefits of technology

The catalyst has achieved low cost and high efficiency synthesis of N,N-dimethylp-toluidine, and the catalyst has excellent catalytic performance and stability and has industrial prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386864A_ABST
    Figure CN119386864A_ABST
Patent Text Reader

Abstract

The invention relates to a non-noble metal catalyst Cu / TiO2-P25, a preparation method thereof and application of the non-noble metal catalyst Cu / TiO2-P25 in synthesis of N, N-dimethyl-p-toluidine from formaldehyde and N-methylaniline, and belongs to the field of catalysts. According to the catalyst, copper nitrate trihydrate serves as a copper source, P25 type TiO2 serves as a carrier, metal is loaded on the P25 type TiO2 through a deposition-precipitation method, the catalyst Cu / TiO2-P25 is obtained through hydrogen reduction in a tubular furnace, then the catalyst Cu / TiO2-P25 is dispersed in a solvent, and hydrogen serves as a hydrogen source to catalyze formaldehyde and N-methylaniline to synthesize N, N-dimethyl p-toluidine. Wherein the Cu / TiO2-P25 catalyst with the copper content of 6% has excellent catalytic performance, and when the hydrogen pressure is 3.5 MPa, the temperature is 180 DEG C and the reaction is performed for 8 hours, the conversion rate of N-methylaniline reaches 100%, and the selectivity on N, N-dimethyl-p-toluidine is 50.8%. The preparation method is simple and low in production cost, is used for catalyzing formaldehyde and N-methylaniline to synthesize N, N-dimethyl-p-toluidine, and has a wide industrialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal catalysts, and specifically relates to a non-noble metal catalyst Cu / TiO2-P25 and a preparation method thereof, and an application thereof in synthesizing N,N-dimethyl-p-toluidine in a heterogeneous system. Background Art

[0002] N,N-dimethyl-p-toluidine, molecular formula is C9H 13 N, is a light yellow liquid with a relative molecular weight of 135.21, a melting point of -25°C, a boiling point of 211°C, and is soluble in organic solvents such as water, ethanol, and chloroform. In organic synthesis, N,N-dimethyl-p-toluidine is often used as a catalyst, reducing agent, and intermediate. N,N-dimethyl-p-toluidine can also be used to prepare dyes, pigments, and photosensitive materials. In the medical field, N,N-dimethyl-p-toluidine has certain biological activity and can be used as a synthetic raw material for antibacterial and anti-tumor drugs. In addition to the above application fields, N,N-dimethyl-p-toluidine is also widely used in the field of organic electronics. It can be used as a component of organic semiconductor materials for the manufacture of organic thin film transistors and organic light-emitting diodes as well as organic solar cells and other devices. In summary, N,N-dimethyl-p-toluidine is an important organic compound with a wide range of applications and research value.

[0003] N,N-dimethyl-p-toluidine is usually synthesized by N-methylation of N-methyl-p-toluidine. For example, Lin et al. used a deposition-precipitation method to disperse PdZn alloy particles on the surface of TiO2 and successfully prepared Pd-ZnO / TiO2 catalyst, and applied the catalyst to the N-methylation reaction of N-methyl-p-toluidine with CO2 and H2. The yield of N,N-dimethyl-p-toluidine reached 90.8%. Kon et al. x Pt-MoO was prepared by co-loading on TiO2 x / TiO2 catalyst, in the N-methylation reaction with N-methyl-p-toluidine as substrate, the yield of N,N-dimethyl-p-toluidine reached 85%, indicating that Pt-MoO x / TiO2 catalyst has good catalytic performance. Toyao et al. synthesized Re / TiO2 catalyst by impregnation method. Under the condition of no additives, the yield of synthesizing N,N-dimethyl-p-toluidine by N-methyl-p-toluidine was 92%. Dong prepared a cheap heterogeneous CuAl2O3 catalyst by in situ topological transformation method, which was applied to the catalytic synthesis of N,N-dimethyl-p-toluidine from p-nitrotoluene. The catalyst also showed strong stability and could be easily separated for continuous reuse. These synthetic routes have high raw material costs, while the synthesis of N,N-dimethyl-p-toluidine using N-methylaniline and formaldehyde as raw materials has low production cost and good application prospects. Summary of the invention

[0004] In view of the above problems existing in the existing catalytic synthesis of N,N-dimethyl-p-toluidine, the purpose of the present invention is to provide a non-precious metal catalyst Cu / TiO2-P25 and a preparation method thereof, as well as the application of synthesizing N,N-dimethyl-p-toluidine in a heterogeneous system. The preparation method is simple, the production cost is low, and it has industrial prospects.

[0005] To achieve the above purpose, the present invention adopts the following technical solutions.

[0006] One of the purposes of the present invention is to provide a highly active catalyst Cu / TiO2-P25, wherein Cu is loaded on P25 type TiO2, and the loading amount of Cu is 2-10wt% of the catalyst.

[0007] Preferably, the Cu loading is 6 wt % of the catalyst.

[0008] In the Cu / TiO2-P25 catalyst, the Cu loading is expressed as a mass percentage, which is directly abbreviated as 2-10% in the subsequent content of this article, and its meaning is the same as the 2-10wt% recorded in this article.

[0009] Another object of the present invention is to provide a method for preparing the highly active catalyst Cu / TiO2-P25, the specific steps of which are as follows:

[0010] (1) P25 TiO2 and copper nitrate trihydrate were added to pure water and stirred evenly. The resulting suspension was placed in a constant temperature water bath and stirred vigorously. A precipitant - Na2CO3 solution was added dropwise to adjust the pH to alkaline. The resulting mixture was stirred for 2 hours and allowed to stand for 30 minutes to form a precipitate.

[0011] (2) collecting the precipitate, washing it to a pH of 7, and then drying it in a vacuum drying oven at 60° C. for 12 h to obtain unreduced Cu / TiO2-P25;

[0012] (3) The unreduced catalyst Cu / TiO2-P25 is placed in a tubular furnace, heated and reduced under a hydrogen atmosphere, and naturally cooled to room temperature to obtain Cu / TiO2-P25.

[0013] Preferably, the copper salt used in step (1) is one of copper nitrate trihydrate, copper sulfate or copper chloride.

[0014] In this preferred embodiment, since they are all divalent copper salts, the technical effects are the same.

[0015] Preferably, in step (1), the molar ratio of P25-type TiO2 to copper nitrate trihydrate is 8-40:1.

[0016] Preferably, the temperature of the water bath in step (1) is 50-70°C.

[0017] Preferably, in step (1), the concentration of the Na2CO3 solution is 0.1 g / mL.

[0018] Preferably, in step (1), a precipitant-Na2CO3 solution is added dropwise to adjust the pH to 8-10.

[0019] Preferably, in step (3), the heating rate of the tubular furnace is 5°C / min, the reduction temperature in the tubular furnace is 200-400°C, and the reduction time is 1.5-2.5h.

[0020] Another object of the present invention is to provide the high-activity catalyst Cu / TiO2-P25 for catalytic synthesis of N,N-dimethyl-p-toluidine in a heterogeneous system. After 8 hours of reaction, the conversion rate of N-methylaniline reaches 100%, and the selectivity for N,N-dimethyl-p-toluidine is 50.8%.

[0021] The specific steps of catalyzing the synthesis of N,N-dimethyl-p-toluidine by the non-precious metal catalyst Cu / TiO2-P25 in a heterogeneous system are as follows:

[0022] (1) Select a stainless steel high-pressure reactor and insert a glass container as the reactor lining;

[0023] (2) Weighing the catalyst Cu / TiO2-P25 into a high-pressure reactor, weighing formaldehyde and N-methylaniline and dissolving them in n-octane solvent, and placing the mixed solution in the high-pressure reactor after ultrasonic dispersion;

[0024] (3) After sealing the reactor, evacuate it three times with hydrogen at a pressure of 1 MPa, maintain the hydrogen pressure at 1 MPa at room temperature, and check the airtightness of the reactor;

[0025] (4) First, heat the reactor to 180°C, continue to introduce hydrogen to 3.5 MPa, maintain the temperature and pressure in the reactor and react for 1 hour;

[0026] (5) After the reaction is completed and cooled to room temperature, open the gas valve of the high-pressure reactor and release the gas in the reactor until the pressure reaches 0, completing the reaction process.

[0027] After the reaction is completed, the reaction solution is filtered and injected into a gas chromatograph using a micro-injection needle. Using n-dodecane as an internal standard, the conversion rate of N-methylaniline and the selectivity of N,N-dimethyl-p-toluidine catalyzed by the catalysts of different embodiments are calculated by gas chromatography.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1) The present invention adopts a deposition-precipitation method to prepare Cu / TiO2-P25, which uses non-precious metals as active phases and P25-type TiO2 as a carrier, which greatly reduces the cost of raw materials and is green and environmentally friendly;

[0030] 2) The present invention uses formaldehyde and N-methylaniline as reaction substrates to synthesize N,N-dimethyl-p-toluidine, has a simple method, low production cost, and has industrial prospects.

[0031] 3) The 6% Cu / TiO2-P25 catalyst prepared by the preparation method of the present invention has excellent catalytic performance; under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180°C, reaction time 8h, and catalyst 50mg, the conversion rate of N-methylaniline reaches 100%, and the selectivity for N,N-dimethyl-p-toluidine is 50.8%. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the XRD pattern of the Cu / TiO2-P25 catalyst prepared in Example 3.

[0033] Figure 2 This is a time course chart of the Cu / TiO2-P25 catalyst prepared in Example 3.

[0034] Figure 3 This is the performance diagram of the stability experiment of the Cu / TiO2-P25 catalyst prepared in Example 3.

[0035] Figure 4 This is the TEM image of the Cu / TiO2-P25 catalyst prepared in Example 3. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further described below with reference to specific embodiments, but the protection scope of the present invention is not limited thereto.

[0037] The present invention uses different proportions of Cu loaded on P25 type TiO2 to prepare Cu / TiO2-P25 as an example to detect the performance and parameters of the product and determine the optimal performance of the product.

[0038] In the following specific examples 1-5, the catalyst was prepared using the following steps:

[0039] (1) P25 TiO2 and copper nitrate trihydrate were added to pure water and stirred evenly. The resulting suspension was placed in a 60°C water bath and stirred vigorously. A precipitant Na2CO3 solution with a concentration of 0.1 g / mL was added dropwise to adjust the pH to 9. The resulting mixture was stirred for 2 hours and allowed to stand for 30 minutes to form a precipitate.

[0040] (2) collecting the precipitate, washing it to a pH of 7, and then drying it in a vacuum drying oven at 60° C. for 12 h to obtain unreduced Cu / TiO2-P25;

[0041] (3) The unreduced catalyst Cu / TiO2-P25 was placed in a tubular furnace and heated for reduction for 2 h in a hydrogen atmosphere at a heating rate of 5°C / min to 300°C for 2 h, and then naturally cooled to room temperature to obtain Cu / TiO2-P25.

[0042] Among them, in the amount of raw materials, by controlling the ratio of P25 type TiO2 and copper salt, specifically the molar ratio of copper nitrate trihydrate is 8-40:1. , Cu can be loaded in the catalyst in different proportions.

[0043] The application test of the catalyst prepared by the above method in the catalytic synthesis of N, N-dimethyl-p-toluidine is as follows: it is carried out in a 200mL stainless steel autoclave, and a glass container is inserted as the lining of the autoclave; 50mg of the catalyst is weighed into the autoclave, and then 1mmol of N-methylaniline, 2mmol of formaldehyde and 20mL of n-octane are weighed, and N-methylaniline and formaldehyde are dissolved in n-octane, and the mixed solution is placed in the autoclave after ultrasonic dispersion. After sealing the reactor, it is emptied three times with hydrogen (1MPa), and the hydrogen pressure is increased by 1MPa at room temperature, and the air tightness is checked. After checking the air tightness, the magnetic speed is modulated to 550rpm, and when the temperature of the autoclave is raised to 180℃, hydrogen is introduced until the pressure reaches 3.5MPa, and the timing is started. After the reaction is allowed to proceed for 1h, after cooling to room temperature, the air valve of the autoclave is opened, and the gas in the autoclave is released until the pressure is 0MPa.

[0044] After filtering the reaction solution, use a micro-injection needle to draw 0.4 μL and inject it into the gas chromatograph. The gas chromatograph hydrogen flow rate is set to 40-60 mL / min, the air flow rate is 200-300 mL / min, and the carrier gas flow rate is 2-3 mL / min. The injection temperature is set to 280.0°C, the initial temperature of the column furnace is set to 130°C and maintained for 10 minutes, then heated to 220°C at 25°C / min and maintained for 10 minutes, and the FID temperature is set to 280.0°C. Using n-dodecane as the internal standard, the conversion rate of N-methylaniline catalyzed by the catalysts of different embodiments and the selectivity of N,N-dimethyl-p-toluidine are calculated by gas chromatography.

[0045] Example 1: Application of 2% Cu / TiO2-P25 in the catalytic synthesis of N,N-dimethyl-p-toluidine

[0046] The catalyst of Example 1 of the present invention was tested for catalytic synthesis of N,N-dimethyl-p-toluidine, and the performance test conditions and results are as follows:

[0047] Under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180°C, reaction time 1h, catalyst 50mg, formaldehyde 2mmol, N-methylaniline 1mmol, the catalyst conversion rate was 70.7% and the selectivity of N,N-dimethyl-p-toluidine was 11.6%.

[0048] Example 2: Application of 4% Cu / TiO2-P25 in the catalytic synthesis of N,N-dimethyl-p-toluidine

[0049] The catalyst of Example 2 of the present invention was tested for catalytic synthesis of N,N-dimethyl-p-toluidine, and the performance test conditions and results are as follows:

[0050] Under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180°C, reaction time 1h, catalyst 50mg, formaldehyde 2mmol, N-methylaniline 1mmol, the catalyst conversion rate was 79.4% and the selectivity of N,N-dimethyl-p-toluidine was 14.3%.

[0051] Example 3: Application of 6% Cu / TiO2-P25 in the catalytic synthesis of N,N-dimethyl-p-toluidine

[0052] The catalyst of Example 3 of the present invention was tested for catalytic synthesis of N,N-dimethyl-p-toluidine, and the performance test conditions and results are as follows:

[0053] Under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180°C, reaction time 1h, catalyst 50mg, formaldehyde 2mmol, N-methylaniline 1mmol, the catalyst conversion rate was 86.5% and the selectivity of N,N-dimethyl-p-toluidine was 18.2%.

[0054] Example 4: Application of 8% Cu / TiO2-P25 in the catalytic synthesis of N,N-dimethyl-p-toluidine

[0055] The catalyst of Example 4 of the present invention was tested for catalytic synthesis of N,N-dimethyl-p-toluidine, and the performance test conditions and results are as follows:

[0056] Under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180°C, reaction time 1h, catalyst 50mg, formaldehyde 2mmol, N-methylaniline 1mmol, the catalyst conversion rate was 83.1% and the selectivity of N,N-dimethyl-p-toluidine was 12.7%.

[0057] Example 5: Application of 10% Cu / TiO2-P25 in the catalytic synthesis of N,N-dimethyl-p-toluidine

[0058] The catalyst of Example 5 of the present invention was tested for catalytic synthesis of N,N-dimethyl-p-toluidine, and the performance test conditions and results are as follows:

[0059] Under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180°C, reaction time 1h, catalyst 50mg, formaldehyde 2mmol, N-methylaniline 1mmol, the catalyst conversion rate was 75.5% and the selectivity of N,N-dimethyl-p-toluidine was 9.8%.

[0060] Comparative Example 1: Application of 6% Cu / ZnO in the catalytic synthesis of N,N-dimethyl-p-toluidine

[0061] The 6% Cu / ZnO of this comparative example 1 was used for catalytic synthesis of N,N-dimethyl-p-toluidine, and the performance test conditions and results were as follows:

[0062] Under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180°C, reaction time 1h, catalyst 50mg, formaldehyde 2mmol, N-methylaniline 1mmol, the catalyst conversion rate was 32.4% and the selectivity of N,N-dimethyl-p-toluidine was 1.3%.

[0063] Comparative Example 2: Application of 6% Cu / CeO2 in the catalytic synthesis of N,N-dimethyl-p-toluidine

[0064] The 6% Cu / CeO2 of this comparative example 2 was used for catalytic synthesis of N,N-dimethyl-p-toluidine, and the performance test conditions and results were as follows:

[0065] Under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180°C, reaction time 1h, catalyst 50mg, formaldehyde 2mmol, N-methylaniline 1mmol, the catalyst conversion rate was 25.8% and the selectivity of N,N-dimethyl-p-toluidine was 1.7%.

[0066] Example 6: Application of 6% Cu / TiO2-P25 in the catalytic synthesis of N,N-dimethyl-p-toluidine

[0067] The catalyst of Example 6 of the present invention is prepared by reduction at a hydrogen reduction temperature of 200° C., and then subjected to a catalytic synthesis of N,N-dimethyl-p-toluidine application test. The performance test conditions and results are as follows:

[0068] Under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180°C, reaction time 1h, catalyst 50mg, formaldehyde 2mmol, N-methylaniline 1mmol, the catalyst conversion rate was 82.3% and the selectivity of N,N-dimethyl-p-toluidine was 16.7%.

[0069] Example 7: Application of 6% Cu / TiO2-P25 in the catalytic synthesis of N,N-dimethyl-p-toluidine

[0070] The catalyst of Example 7 of the present invention is prepared by reduction at a hydrogen reduction temperature of 400° C., and then subjected to an application test for catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:

[0071] Under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180°C, reaction time 1h, catalyst 50mg, formaldehyde 2mmol, N-methylaniline 1mmol, the catalyst conversion rate was 84.8% and the selectivity of N,N-dimethyl-p-toluidine was 15.2%.

[0072] Example 8: Application of 6% Cu / TiO2-P25 in the catalytic synthesis of N,N-dimethyl-p-toluidine

[0073] The catalyst of Example 8 of the present invention was prepared at a water bath temperature of 50° C., and then subjected to a catalytic synthesis of N,N-dimethyl-p-toluidine application test. The performance test conditions and results are as follows:

[0074] Under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180°C, reaction time 1h, catalyst 50mg, formaldehyde 2mmol, N-methylaniline 1mmol, the catalyst conversion rate was 84.9% and the selectivity of N,N-dimethyl-p-toluidine was 16.8%.

[0075] Example 9: Application of 6% Cu / TiO2-P25 in the catalytic synthesis of N,N-dimethyl-p-toluidine

[0076] The catalyst of Example 9 of the present invention was prepared at a water bath temperature of 70° C., and then subjected to a catalytic synthesis of N,N-dimethyl-p-toluidine application test. The performance test conditions and results are as follows:

[0077] Under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180°C, reaction time 1h, catalyst 50mg, formaldehyde 2mmol, N-methylaniline 1mmol, the catalyst conversion rate was 85.6% and the selectivity of N,N-dimethyl-p-toluidine was 17.1%.

[0078] Example 10: Application of 6% Cu / TiO2-P25 in the catalytic synthesis of N,N-dimethyl-p-toluidine

[0079] The catalyst of Example 10 of the present invention is prepared when the pH of the solution is 7, and then the catalyst is tested for catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:

[0080] Under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180°C, reaction time 1h, catalyst 50mg, formaldehyde 2mmol, N-methylaniline 1mmol, the catalyst conversion rate was 75.1% and the selectivity of N,N-dimethyl-p-toluidine was 11.5%.

[0081] Example 11: Application of 6% Cu / TiO2-P25 in the catalytic synthesis of N,N-dimethyl-p-toluidine

[0082] The catalyst of Example 11 of the present invention is prepared when the pH of the solution is 8, and then the catalyst is tested for catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:

[0083] Under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180°C, reaction time 1h, catalyst 50mg, formaldehyde 2mmol, N-methylaniline 1mmol, the catalyst conversion rate was 83.4% and the selectivity of N,N-dimethyl-p-toluidine was 15.8%.

[0084] Example 12: Application of 6% Cu / TiO2-P25 in the catalytic synthesis of N,N-dimethyl-p-toluidine

[0085] The catalyst of Example 12 of the present invention is prepared when the pH of the solution is 10, and then the catalyst is tested for catalytic synthesis of N,N-dimethyl-p-toluidine. The performance test conditions and results are as follows:

[0086] Under the reaction conditions of hydrogen pressure 3.5MPa, temperature 180°C, reaction time 1h, catalyst 50mg, formaldehyde 2mmol, N-methylaniline 1mmol, the catalyst conversion rate was 86.3% and the selectivity of N,N-dimethyl-p-toluidine was 17.5%.

[0087] The catalyst prepared in Example 3 was subjected to a spectrum test, an electron microscope scan, a catalytic activity test and a stability test, and the test results are as follows.

[0088] Figure 1 This is the XRD pattern of the catalyst prepared in Example 3. Compared with the JCPDS standard data, it can be observed that the characteristic peak of P25 is obvious, and the characteristic peak belonging to the Cu (111) crystal plane can be observed in the spectrum, and the size of the Cu particles in the catalyst is 12 nm.

[0089] Figure 2The Time course diagram of the catalyst prepared in Example 3 shows that when the reaction times are 0 h, 1 h, 2 h, 4 h, 6 h and 8 h, the conversion of N-methylaniline is 62.2%, 86.5%, 95.8%, 100%, 100%, and 100.0%, respectively, and the selectivity of N,N-dimethyl-p-toluidine is 7.8%, 18.2%, 25.4%, 37.2%, 45.6% and 50.8%, respectively. It can be concluded that the catalyst prepared in Example 3 has higher catalytic activity.

[0090] Figure 3 The stability experimental performance diagram of the catalyst prepared in Example 3 shows that when the catalyst is cycled for the first, second, third and fourth times, the conversion rates of N-methylaniline are 86.5%, 87.2%, 85.1% and 84.5%, respectively, and the selectivities of N,N-dimethyl-p-toluidine are 18.2%, 17.7%, 17.4% and 16.9%, respectively. It can be concluded that the catalyst has high stability, can be used repeatedly, and has high industrial production and application value.

[0091] Figure 4 This is the TEM image of the catalyst prepared in Example 3. It can be seen from the image that Cu is loaded on P25 type TiO2 and the Cu particle size is 12nm.

[0092] The catalytic performance of the catalyst products obtained by different Cu loading amounts for aniline under the same reaction conditions is shown in Table 1.

[0093] Table 1 Effect of different Cu loadings on catalytic activity

[0094]

[0095] It can be seen from Examples 1 to 5 in Table 1 that the Cu loading has a great influence on the catalyst activity. When the loading content is from 2% to 10%, the conversion rate of N-methylaniline and the selectivity of N,N-dimethyl-p-toluidine first increase and then decrease, which means that the catalytic performance of the catalyst also increases first and then decreases, showing a volcano-shaped trend. When the loading amount is 6% and the reaction time is 1h, the conversion rate of N-methylaniline reaches a maximum of 86.5%, and the selectivity for N,N-dimethyl-p-toluidine is 18.2%.

[0096] The catalytic performance of the catalyst products obtained by using different carriers for aniline under the same reaction conditions is shown in Table 2.

[0097] Table 2 Effect of different carriers on catalyst activity

[0098]

[0099] It can be seen from Example 3, Comparative Example 1 and Comparative Example 2 in Table 2 that different types of carriers have a great influence on the activity of the catalyst, and the carrier TiO2-P25 has a significant promoting effect on the catalytic performance of the catalyst and can significantly improve the catalytic performance of the catalyst.

[0100] The catalytic performance of the catalyst products obtained by different hydrogen reduction temperatures on aniline under the same reaction conditions is shown in Table 3.

[0101] Table 3 Effect of different hydrogen reduction temperatures on catalyst activity

[0102]

[0103] It can be seen from Example 3, Example 6 and Example 7 in Table 3 that the reduction temperature of hydrogen has a great influence on the performance of the catalyst. As the reduction temperature increases from 200°C to 400°C, the catalytic performance of the catalyst first increases and then decreases. When the reduction temperature is 300°C, the catalytic performance of the catalyst reaches the highest.

[0104] The catalytic performance of the catalyst products obtained by different water bath heating temperatures on aniline under the same reaction conditions is shown in Table 4.

[0105] Table 4 Effect of different water bath heating temperatures on catalyst activity

[0106]

[0107] It can be seen from Example 3, Example 8 and Example 9 in Table 4 that during the preparation of the catalyst, the heating temperature of the water bath has a certain influence on the performance of the catalyst, but the influence is not significant. Too high or too low a water bath temperature will weaken the activity of the prepared catalyst. When the water bath heating temperature is 60°C, the catalyst has the strongest activity.

[0108] The catalytic performance of the catalyst products obtained under different solution pH conditions on aniline under the same reaction conditions is shown in Table 5.

[0109] Table 5 Effect of different pH of solution on the activity of catalyst

[0110]

[0111] It can be seen from Example 3 and Example 10 to Example 12 in Table 5 that in the preparation process of the catalyst, the pH of the solution is adjusted by the precipitant-Na2CO3 solution. The pH of the solution has a significant effect on the activity of the catalyst. If the solution is neutral, the activity of the catalyst is greatly weakened. When the solution is alkaline, the activity of the catalyst is significantly enhanced. As the alkalinity increases, the activity of the catalyst first increases and then weakens. When the pH of the solution is 9, the prepared catalyst has the strongest activity.

[0112] The above description is only part of the embodiments of the present invention and is not intended to limit the present invention. All equivalent changes and modifications made according to the content of the present invention are within the protection scope of the present invention.

Claims

1. A non-precious metal catalyst Cu / TiO2-P25, characterized in that: Cu is supported on P25 type TiO2, and the Cu loading is 2-10 wt% of the catalyst.

2. The non-precious metal catalyst Cu / TiO2-P25 according to claim 1, characterized in that: The Cu loading was 6 wt% of the catalyst.

3. A method for preparing the highly active catalyst Cu / TiO2-P25 as described in any one of claims 1 to 2, characterized in that: The specific steps are as follows: (1) P25 TiO2 and copper nitrate trihydrate were added to pure water and stirred evenly. The resulting suspension was placed in a constant temperature water bath and stirred vigorously. A precipitant - Na2CO3 solution was added dropwise to adjust the pH to alkaline. The resulting mixture was stirred for 2 hours and allowed to stand for 30 minutes to form a precipitate. (2) collecting the precipitate, washing it to a pH of 7, and then drying it in a vacuum drying oven at 60° C. for 12 h to obtain unreduced Cu / TiO2-P25; (3) The unreduced catalyst Cu / TiO2-P25 is placed in a tubular furnace, heated and reduced under a hydrogen atmosphere, and naturally cooled to room temperature to obtain Cu / TiO2-P25.

4. The method for preparing the highly active catalyst Cu / TiO2-P25 according to claim 3, characterized in that: The copper salt used in step (1) is one of copper nitrate trihydrate, copper sulfate or copper chloride.

5. The method for preparing the highly active catalyst Cu / TiO2-P25 according to claim 3, characterized in that: In the step (1), the molar ratio of P25-type TiO2 to copper salt is 8-40:

1.

6. The method for preparing the highly active catalyst Cu / TiO2-P25 according to claim 3, characterized in that: The temperature of the water bath in step (1) is 50-70°C.

7. The method for preparing the non-precious metal catalyst Cu / TiO2-P25 according to claim 3, characterized in that: In the step (1), the concentration of the Na2CO3 solution is 0.1 g / mL.

8. The method for preparing the non-precious metal catalyst Cu / TiO2-P25 according to claim 3, characterized in that: In the step (1), a precipitant-Na2CO3 solution is added dropwise to adjust the pH to 8-10.

9. The method for preparing the non-precious metal catalyst Cu / TiO2-P25 according to claim 3, characterized in that: In the step (3), the heating rate of the tubular furnace is 5°C / min, the reduction temperature in the tubular furnace is 200-400°C, and the reduction time is 1-3h.

10. Use of the non-precious metal catalyst Cu / TiO2-P25 as described in any one of claims 1 to 2 in the synthesis of N,N-dimethyl-p-toluidine in a heterogeneous system, wherein the conversion rate of N-methylaniline reaches 100% after 8 hours of reaction, and the selectivity for N,N-dimethyl-p-toluidine is 50.8%.

Citation Information

Patent Citations

  • Non-noble metal catalyst Cu-ZnO / TiO2, preparation method thereof and application of non-noble metal catalyst Cu-ZnO / TiO2 in catalysis of N-methylation of N-methylaniline in heterogeneous system

    CN118287085A

  • High-activity catalyst Cu-ZnO / TiO2-P25, preparation method thereof and application of high-activity catalyst Cu-ZnO / TiO2-P25 in N-methylated aniline in heterogeneous system

    CN118384888A

  • Method of producing metal

    JP2004149900A

Cited By

  • The invention relates to a non-noble metal catalyst Cu-ZnO / TiO2-P25, which is used for catalytically synthesizing N, Napos in a heterogeneous system. Application of-dicyclohexyl p-phenylenediamine

    CN120169372A